THE IMPLEMENTATION OF EXTENSIVE READING IN THE THIRD SEMESTER STUDENT OF ENGLISH DEPARTMENT UNIVERSITAS BANDAR LAMPUNG IN ACADEMIC YEAR 2017-2018 - Muhammad Wahyudi; Helta Anggia (Universitas Bandar Lampung, 2017)
This research is based on the researcher’s experience as a student of college in learning English. Most of the students were got failed in motivation to read in class, it happened because we used to give a reading text that we don’t know and we don’t like it. It make us become lazy to read the material of reading text which is given because of lack of motivation that happened. In the end we often can’t get the point of the idea of the reading text that given and felt that the problems have influenced our reading rate become stuck, or there are no improvements. The researcher chose a method extensive reading to overcome the problem. This research is aimed to know how the improvement of extensive reading approach on the reading motivation, reading rate in the third semester student of English Department Universitas Bandar Lampung studying English as a foreign language. The students’ motivation and reading rate improved after the implementation of extensive reading. By this method the students were asked to inculate reading habits behaviour, so the students like reading more and motivated to read than before. This research was qualitative mthod using three indicators observation, questionnaire and interview. The subject of research consisted of 41 students of the third semester students of English Department Universitas Bandar Lampung. The result showed that extensive reading method could motivate the students to get better achievement in reading. Such as: extensive reading helped them improve their reading rate and motivation to read.